Thermal decomposition of hydrated selenites of trivalent lanthanides and yttrium - Ionashiro, Massao [UNESP]; Melios, C. B.; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Giolito, I (Elsevier B.V., 1990)
Hydrated lanthanide(III) and yttrium(III) selenites were prepared. Simultaneous thermogravimetric and differential thermal analysis, classical differential thermal analysis, X-ray diffraction and other methods of analysis have been used in the characterisation as well as in the study of the thermal decomposition of these compounds. The results led to the composition and thermal stability and also to interpretations concerning the thermal decomposition mechanisms. © 1990.